2016
DOI: 10.1002/chem.201601253
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Reactivity of Gold Nanoparticles Towards Benzimidazole‐2‐ylidene Ligands

Abstract: The reactivity of benzimidazol-2-ylidenes with respect to gold nanoparticles (AuNPs) has been investigated using a combined experimental and computational approach. First, the grafting of benzimidazol-2-ylidenes bearing benzyl groups on the nitrogen atoms is described, and comparisons are made with structurally similar N-heterocyclic carbenes (NHCs) bearing other N-groups. Similar reactivity was observed for all NHCs, with 1) the erosion of the AuNPs under the effect of the NHC and 2) the formation of bis(NHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 125 publications
11
38
0
Order By: Relevance
“…We assume that the multiple hetero metal–metal bonds induce a variety of slightly different electronic states, which results in a variety of chemical shifts for the carbenic carbon atom. Additionally, nonequivalent environments of the ligands on the NPs can induce signal splitting in the 13 C NMR spectra, as predicted by Richeter and co‐workers using DFT calculations for NHC‐functionalized Au 38 clusters …”
Section: Resultsmentioning
confidence: 99%
“…We assume that the multiple hetero metal–metal bonds induce a variety of slightly different electronic states, which results in a variety of chemical shifts for the carbenic carbon atom. Additionally, nonequivalent environments of the ligands on the NPs can induce signal splitting in the 13 C NMR spectra, as predicted by Richeter and co‐workers using DFT calculations for NHC‐functionalized Au 38 clusters …”
Section: Resultsmentioning
confidence: 99%
“…Rodríguez‐Castillo et al. concluded from DFT calculations that upright NHCs restructure Au surface atoms, probably as an intermediate step in the formation of (NHC) 2 Au I complexes . Additionally, Tang and Jiang recently reported that (NHC) 2 Au complexes containing less sterically bulky NHCs favor flat lying NHC geometries driven by vdW interactions between the NHCs and the Au surface .…”
Section: Figurementioning
confidence: 99%
“…In the solid‐state 13 C NMR spectra (Figure a, blue line, Figure S50, Supporting Information), peaks for C Ar (135 ppm, aromatic rings) and C Me (35 ppm, N‐methyl groups and bridging methylene) in the POMPs correspond well with those observed in bis‐NHC‐Ir 4a . However, the broad signals for C NHC and C CO (≈190 ppm) are uncertainly assigned, even with more than 100 mg samples, due to the extremely low NHC content (0.8 % based on Ir) in the POMP matrix of solid 4a . To solve this ambiguous problem, POMP‐NHC‐Ir 1h fabricated via direct knitting with molecular precursor 4a without benzene addition was also investigated by solid‐state 13 C NMR spectroscopy.…”
Section: Fabrication Of Pomp‐nhc‐m By Direct Knitting With Different mentioning
confidence: 99%
“…The absence of IrIr bonds in POMP‐NHC‐Ir 1d (Figure e, Table S1, Supporting Information) implied that the Ir(I) centers are atomically well dispersed in the polymer matrix. Considering that chlorine was found in XPS and EDS studies (Figures S24 and S38, Supporting Information) due to partial exchange of CO ligands with Cl elements of chlorinated solvent and FeCl 3 during the knitting process, IrCl bond was implemented for EXAFS data fitting. The obtained good R‐factor of 0.012 suggested the existence of IrCl bond with small quantity within the polymer matrix.…”
Section: Fabrication Of Pomp‐nhc‐m By Direct Knitting With Different mentioning
confidence: 99%